Crustal studies along Indore-Khandwa section of Narmada basin by deep seismic sounding - SRIVASTAVA, H. N.; VERMA, R. K.; VERMA, G. S. (MAUSAM, 1983)
The area along Indore-Khandwa profile in the M.P. region has been studied using the deep seismic sounding, techniques. A total of eight observatories were set up along the profile to record the explosions data, using high magnification seismographs. The quantity of explosions used for, the purpose ranged from 50 kg to 1200 kg. Refraction studies have revealed that there is a two layer crust consisting of 18 km of granite and 20 km of basalt in the region; that is giving a depth of Moho as 38 km. This has been further confirmed from the reflection studies. Using the velocity model deduced in this paper, the epicentral parameters of micro earthquakes have been determined. It has been found that the seismic activity in the region has been very low during the period of observations.